Student worksheet based on Surakarta’s local wisdom in primary school: A preliminary research - Ratna Widyaningrum; Ema Butsi Prihastari (Universitas Sebelas Maret, 2020)
Student worksheets as one of the learning tools that should be developed by the teacher because textbooks from the government have minimal material. Student worksheets that are integrated with local wisdom can make learning more meaningful. This study aims to describe the results of the preliminary analysis consist of the 2013 curriculum learning process that is implemented in primary school at Banjarsari Surakarta, especially in terms of the needs of student worksheet in the learning process, the steps for making student worksheet based on Surakarta’s local wisdom, and analyzing local wisdom material that will be integrated into making student worksheet. This research used a qualitative descriptive approach. The research subjects were teachers and 5th-grade students, amounting to 2 teachers and 10 students. The sampling technique used was purposive sampling. Data collection techniques using interviews, observation, and documentation. Data validity uses source and method triangulation. Data analysis techniques include reduction, presentation, and conclusion. The results obtained are the teachers generally use simple student worksheets and haven’t been linked to local wisdom. The student worksheet format created only consists of work steps and assessments. The steps of making a student worksheet are curriculum analysis and local wisdom to be used, compiling, determining title, and writing. Local wisdom materials that can be integrated include Laweyan batik, Pasar Gede, medicinal plants, and the Javanese community farming system. The implication of this research is to provide meaningful learning resources for students and instill a sense of love for local culture.